Lay Evaluation of Financial Experts: The Action Advice Effect and Confirmation Bias - Zaleskiewicz, Tomasz; Gasiorowska, Agata; Stasiuk, Katarzyna; Maksymiuk, Renata; Bar-Tal, Yoram (Frontiers in Psychology, 2016)
The goal of this experimental project was to investigate lay peoples’ perceptions of epistemic authority (EA) in the field of finance. EA is defined as the extent to which a source of information is treated as evidence for judgments independently of its objective expertise and based on subjective beliefs. Previous research suggested that EA evaluations are biased and that lay people tend to ascribe higher EA to experts who advise action (in the case of medical experts) or confirm clients’ expectations (in the case of politicians). However, there has been no research into biases in lay evaluations of financial experts and this project is aimed to fill this gap. Experiment 1 showed that lay people tended to ascribe greater authority to financial consultants who gave more active advice to clients considering taking out a mortgage. Experiment 2 confirmed the action advice effect found in Experiment 1. However, the outcomes of Experiments 2 and – particularly – 3 suggested that this bias might also be due to clients’ desire to confirm their own opinions. Experiment 2 showed that the action advice effect was moderated by clients’ own opinions on taking loans. Lay people ascribed the greatest EA to the advisor in the scenario in which he advised taking action and where this coincided with the client’s positive opinion on the advisability of taking out a loan. In Experiment 3 only participants with a positive opinion on the financial product ascribed greater authority to experts who recommended it; participants whose opinion was negative tended to rate consultants who advised rejecting the product more highly. To conclude, these three experiments revealed that lay people ascribe higher EA to financial consultants who advise action rather than maintenance of the status quo, but this effect is limited by confirmation bias: when the client’s a priori opinion is salient, greater authority is ascribed to experts whose advice confirms it. In this sense, results presented in the present paper suggest that the action advice effect might be also interpreted as a specific manifestation of confirmation bias.